Cost-effective desulfurization of acid mine drainage with food waste as an external carbon source: A pilot-scale and long-term study. (10th August 2022) - Yan, Jia; Luo, Fan; Wu, lingyao; Ou, Yinglin; Gong, Changchen; Hao, Tianwei; Huang, Lei; Chen, Yongheng; Long, Jianyou; Xiao, Tangfu; Zhang, Hongguo
Abstract: Sulfate reduction process can be a promising method for simultaneously removing sulfate, metals and metalloids from acid mine drainage (AMD). However, organic matter in AMD is far from enough for sulfate reduction, and an additional carbon source is required, which increases operation costs for AMD treatment. In this study, a two stage AMD treatment system was established (chemical precipitation - sulfate reduction), and food waste hydrolysate was utilized as a carbon source for AMD treatment. Simultaneous removal of sulfate, organics, metals and metalloids was observed in a pilot-scale (10 m 3 ) upflow anaerobic sludge bed (UASB) for over 400 days. Introducing of food waste hydrolysate (FWHS) was not harmful for sulfate reducers in UASB. Decomposition of refractory organic matter in AMD was enhanced after FWHS addition, which led to decreasing of COD concentration (50%) in effluents of UASB. Ten out of 17 organic matter in effluents was no longer detected after FWHS addition. Metals and metalloids from both AMD and FWHS were efficiently removed during the sulfate reduction process (97.7–100%). Volatile fatty acids (acetic and valeric acids) produced during the food waste hydrolysis could be utilized as carbon source for AMD treatment. Interactions among fermentative microbes, sulfate reducers, denitrifiers and methanogens enhanced carbon, sulfur and nitrogen removal in the UASB. Therefore, a cost-effective method for AMD and food waste cotreatment (3.6 kgSO4 2− /kgTS food waste) was established in this study by reducing carbon source addition (100%), biomass production (93%), VFA production (54.5%) and sulfide emission (50%), which might be applied for AMD recycling at mining sites. Graphical abstract: Image 1 Highlights: a two-step fermentation and sulfate reduction coupling process was established. Food waste was used as carbon and nutrients source for acid mine drainage treatment. Sulfate, carbon, metals and metalloids were efficiently removed (87.3–100%). The established technology might be used for acid mine drainage treatment in mines.